EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR - Aryani, Afifah; Rizkasari, Elinda; Irmade, Oka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the efficacy of the Teams Games Tournament (TGT) cooperative learning intervention in accelerating the numeracy competence of fourth-grade elementary school students, specifically within the domain of volume measurement. Adopting a quantitative pre-experimental approach with a One-Group Pretest-Posttest Design, the research involved a sample of fourth-grade students at SDIT Bina Madina recruited via purposive sampling. Data collection was executed using a validated and reliable 20-item multiple-choice numeracy test. Data evaluation encompassed descriptive statistics, the Shapiro-Wilk normality test, paired-samples t-test, and Normalized Gain () calculations. Empirical findings confirmed a statistically significant increase in students' mean numeracy achievement, rising from 67.20 () at pretest to 82.20 () at posttest. The asymptotic Shapiro-Wilk test supported the normal distribution of the dataset (). Inferential testing via paired-samples t-test yielded (), documenting a statistically significant mean disparity following the implementation of the TGT model. The effectiveness estimation recorded an average index of 0.5185 (51.85%), falling within the moderate/effective category. It is concluded that the TGT cooperative strategy is significantly effective in enhancing foundational numeracy literacy. These findings offer practical implications for primary education practitioners to integrate gamified cooperative learning to optimize students' mathematical capabilities